Nghiên cứu mối quan hệ giữa công bằng tổ chức và hành vi công dân trong tổ chức: Vai trò nào cho quá trình trao đổi lãnh đạo - thành viên? - Nguyễn Nhật, Tân (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This study investigates a mediating role of Leader - Member Exchange (LMX) in the linkage between organizational justice (OJ) and organizational citizenship behaviour (OCB). Surveying a sample of 279 employees working in the trade and service sector in Vietnamese SMEs, findings indicated that distributive justice is a stronger predictor of LMX than interactional justice or procedural justice. In addition, LMX has a significant association with altruism, courtesy, civic virtue and conscientiousness. Regarding the relationship between OJ and OCB, interactional justice positively affects all dimensions of OCB. Distributive justice positively impacted civic virtue. Procedural justice also positively affected civic virtue but negatively influenced courtesy and sportsmanship. However, research findings demonstrated that LMX did not act as a mediator in the OJ-OCB relationship. Results of this study have significant implications for HRM practices as it allows organizational managers to initiate appropriate actions to formulate desirable behaviors of subordinates.
Keywords: Organizational justice; Organizational citizenship behaviour; Leader-Member Exchange